2019
DOI: 10.1159/000503928
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Relationship of Transdiagnostic Mood and Psychosis Symptom Domains with Motor Dysfunction

Abstract: Background: A number of motor abnormalities have been reported in psychotic disorders, including dyskinesia and psychomotor slowing. There is also evidence for many of the same motor abnormalities in biological first-degree relatives and accruing evidence for motor abnormalities in bipolar disorder. In addition to motor dysfunction, there are also shared symptom domains amongst these populations. Objectives: We explored the associations of (1) current and lifetime psychosis and mood symptom domains and (2) dom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 71 publications
0
5
0
Order By: Relevance
“…There were 54 studies ( n = 23 461) reporting data on the lifetime prevalence of psychotic symptoms in BD, for an overview of included studies see online Supplementary Material 4: Studies included in the meta-analyses of the lifetime prevalence of psychotic symptoms in bipolar disorders (Aedo et al, 2018; Altindag, Yanik, & Nebioglu, 2006; Atagun et al, 2018; Balzafiore et al, 2017; Berkol, Kirli, Islam, Pinarbasi, & Ozyildirim, 2016; Bolhuis et al, 2021; Burton et al, 2018; Cao et al, 2014; Davila et al, 2006; Dell'Osso et al, 2010, 2015; Ekman et al, 2017; Ernst & Goldberg, 2004; Finseth, Morken, Andreassen, Malt, & Vaaler, 2012; Fuentes, Rizo-Mendez, & Jarne-Esparcia, 2016; Gesi et al, 2016; Goldberg et al, 1999; Gonzalez-Pinto et al, 2011; Grande et al, 2017; Grigoroiu-Serbanescu et al, 2010; Jamra et al, 2010; Javadapour et al, 2010; Karakus & Tamam, 2011; Kent et al, 2020; Kirov & Murray, 1999; Knorr et al, 2021; Laidi et al, 2015; Lee & Kim, 2011; Mantere et al, 2004; Miller et al, 2018; Moon et al, 2012; Nardi et al, 2008; Neves, Malloy-Diniz, Barbosa, Brasil, & Correa, 2009; Newport et al, 2012; Ong et al, 2012; Ortiz et al, 2021; Østergaard, Bertelsen, Nielsen, Mors, & Petrides, 2013; Pacchiarotti et al, 2011; Parker et al, 2013, 2020; Patterson, Sandman, Ring, Jin, & Bunney, 2009; Prabhavathy, Kuruvilla, Ravindren, Ganesh, & Midhun, 2017; Sanchez-Morla et al, 2019; Sarrazin et al, 2018; Savitz et al, 2015; Simonsen et al, 2011; Talati et al, 2013; Tost et al, 2010; Trotti et al, 2020; Tundo et al, 2015; Van Der Werf-Eldering et al, 2011; Van Rheenen et al, 2017; Yazici, Kora, Ucok, Tunali, & Turan, 1999; Yilmaz, Yavuz, Altinbas, Lordoglu, & Kurt, 2015).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…There were 54 studies ( n = 23 461) reporting data on the lifetime prevalence of psychotic symptoms in BD, for an overview of included studies see online Supplementary Material 4: Studies included in the meta-analyses of the lifetime prevalence of psychotic symptoms in bipolar disorders (Aedo et al, 2018; Altindag, Yanik, & Nebioglu, 2006; Atagun et al, 2018; Balzafiore et al, 2017; Berkol, Kirli, Islam, Pinarbasi, & Ozyildirim, 2016; Bolhuis et al, 2021; Burton et al, 2018; Cao et al, 2014; Davila et al, 2006; Dell'Osso et al, 2010, 2015; Ekman et al, 2017; Ernst & Goldberg, 2004; Finseth, Morken, Andreassen, Malt, & Vaaler, 2012; Fuentes, Rizo-Mendez, & Jarne-Esparcia, 2016; Gesi et al, 2016; Goldberg et al, 1999; Gonzalez-Pinto et al, 2011; Grande et al, 2017; Grigoroiu-Serbanescu et al, 2010; Jamra et al, 2010; Javadapour et al, 2010; Karakus & Tamam, 2011; Kent et al, 2020; Kirov & Murray, 1999; Knorr et al, 2021; Laidi et al, 2015; Lee & Kim, 2011; Mantere et al, 2004; Miller et al, 2018; Moon et al, 2012; Nardi et al, 2008; Neves, Malloy-Diniz, Barbosa, Brasil, & Correa, 2009; Newport et al, 2012; Ong et al, 2012; Ortiz et al, 2021; Østergaard, Bertelsen, Nielsen, Mors, & Petrides, 2013; Pacchiarotti et al, 2011; Parker et al, 2013, 2020; Patterson, Sandman, Ring, Jin, & Bunney, 2009; Prabhavathy, Kuruvilla, Ravindren, Ganesh, & Midhun, 2017; Sanchez-Morla et al, 2019; Sarrazin et al, 2018; Savitz et al, 2015; Simonsen et al, 2011; Talati et al, 2013; Tost et al, 2010; Trotti et al, 2020; Tundo et al, 2015; Van Der Werf-Eldering et al, 2011; Van Rheenen et al, 2017; Yazici, Kora, Ucok, Tunali, & Turan, 1999; Yilmaz, Yavuz, Altinbas, Lordoglu, & Kurt, 2015).…”
Section: Resultsmentioning
confidence: 99%
“…The pooled lifetime prevalence of psychotic symptoms in the 51 included DSM BD studies ( N = 8013) was 57% (95% CI 52–62) (Aedo et al, 2018; Altindag et al, 2006; Atagun et al, 2018; Balzafiore et al, 2017; Berkol et al, 2016; Burton et al, 2018; Cao et al, 2014; Davila et al, 2006; Dell'Osso et al, 2010, 2015; Ekman et al, 2017; Ernst & Goldberg, 2004; Finseth et al, 2012; Fuentes et al, 2016; Gesi et al, 2016; Goldberg et al, 1999; Gonzalez-Pinto et al, 2011; Grande et al, 2017; Grigoroiu-Serbanescu et al, 2010; Jamra et al, 2010; Javadapour et al, 2010; Karakus & Tamam, 2011; Kent et al, 2020; Kirov & Murray, 1999; Laidi et al, 2015; Lee & Kim, 2011; Mantere et al, 2004; Miller et al, 2018; Moon et al, 2012; Nardi et al, 2008; Neves et al, 2009; Newport et al, 2012; Ong et al, 2012; Ortiz et al, 2021; Pacchiarotti et al, 2011; Parker et al, 2013, 2020; Patterson et al, 2009; Prabhavathy et al, 2017; Sanchez-Morla et al, 2019; Sarrazin et al, 2018; Savitz et al, 2015; Simonsen et al, 2011; Talati et al, 2013; Tost et al, 2010; Trotti et al, 2020; Tundo et al, 2015; Van Der Werf-Eldering et al, 2011; Van Rheenen et al, 2017; Yazici et al, 1999; Yilmaz et al, 2015).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…According to findings from previous neuroimaging studies, it has been proposed that abnormalities in the sensorimotor domain are related to the dysfunction of the cerebello-thalamo-corticocerebellar network [45]. Additionally, it has been reported that psychomotor slowing is positively related to negative symptoms and mania, regardless of the diagnostic category, among individuals with schizophrenia, schizoaffective disorder, bipolar disorder, and others [46]. Thus, it can be proposed that motor retardation may be the dimensionally defined core constitute of the psychonectome underpinned by the neural network (i.e., the cerebello-thalamo-cortico-cerebellar network) in Asian patients with schizophrenia.…”
Section: Discussionmentioning
confidence: 99%
“…Ristanovic et al [8] tested the association between motor abnormalities and cognition in subjects with nonclinical psychosis. Likewise, Kent et al [9] investigated the association of motor behavior with psychopathological dimensions in a sample of 149 subjects including schizophrenia, schizoaffective disorder, bipolar disorder, relatives, and healthy subjects.…”
mentioning
confidence: 99%